A simple method for choosing the parameters of a two degree-of-freedom tuned vibration absorber - Jang, S. -J.; Brennan, M. J. [UNESP]; Rustighi, E.; Jung, H. -J. (Academic Press Ltd Elsevier B.V. Ltd, 2012)
In this paper a new method for choosing the parameters of a Two degree-of-freedom (dof) tuned vibration absorber (TVA) with translational and rotational degrees of freedom is described. The dynamic stiffness approach is used to model the device, which is constrained to move in the translational direction and to rotate. The choice of the parameters involves a procedure similar to that proposed by Den Hartog in the optimization of a single dof TVA, in which the invariant (fixed) points of the frequency response function of the TVA and the host structure are used to determine the stiffness of the TVA for a given mass. In this paper the approach is extended and applied to the design of a 2dof TVA, and a numerical procedure is used to determine the optimum amount of damping. The method is simple and easy to implement. A numerical example is presented to compare the performance of the 2dof TVA designed using the method described here with the optimal 2dof TVA. It is shown that the performances of the TVAs are similar, validating the new approach. (C) 2012 Elsevier Ltd. All rights reserved.